Impacts of electronic device use on adolescents' sexual knowledge, attitude and perception during the COVID-19 pandemic: A representative sexuality survey - Tse, Desiree Man-Sik; Kiu, Omar Tsui Wai; Yeo, Victoria Anna; Kiu, Elkie Chan Yu; Yip, Paul; Ip, Patrick; Choi, Edmond Pui Hang; Wong, William Chi Wai (Frontiers in Public Health, 2023)
Background COVID-19 pandemic has led to school closure and social distancing measures for infection control. Many young people thus spent more time on electronic devices and the Internet. This study aimed to determine if and how sexual knowledge, perception and behavior as well as sexuality among Hong Kong adolescents were affected as a result. Methods Youth Sexuality Study conducted by The Family Planning Association of Hong Kong (FPAHK) evaluated the sexual knowledge, attitudes and behaviors and sexual health of youth every 5 years since 1981 with adaptations made to the changing environment. We analyzed this cross-sectional data on sexual knowledge, attitude, and experiences as well as the impacts of COVID-19 on daily life, health and relationships. Univariate analysis was conducted to investigate the relationships between the time spent on electronic devices and sexuality, while mediation analyses using the PROCESS procedure were performed to further explore differences in time spent on electronic devices. Results During the COVID-19 pandemic, the majority of our participants spent more time on social media and browsing the Internet on electronic devices with less time for extracurricular activities and learning. Nonetheless, there was better overall sexual knowledge and a lower degree of sexual stigma with a higher overall acceptance of sexual minorities. The mediation analyses found that sexual content [Conditional effect = 0.024 (95% CI 0.008, 0.043)] and engagement online [Conditional effect = 0.036 (CI 0.021, 0.053)] could indirectly influence the effect of screen time on the frequency of sexual practices. Conclusion Policymakers and frontline professionals should re-examine the pedagogy of the present sex education and consider online sex education as the key mode of delivery while guiding the proper use of electronic devices in the learning and exploration of sexual knowledge.